Hubungan Jenis Kelamin dan Riwayat Keluarga dengan Kejadian Hipertensi Pada Pra Lansia di Wilayah Kerja Puskesmas Leuwigajah 2021 - teguh akbar; Suhat; Alysia Margaretta (JURNAL KESEHATAN KARTIKA, 2022)
Hypertension is a condition where systolic blood pressure is more than 140 mmHg and/or diastolic blood pressure is more than 90 mmHg. One of the factors for the occurrence of hypertension include gender and family history. The purpose of this study was to determine the relationship between gender and family history with the incidence of hypertension in pre-elderly in the working area of ​​Leuwigajah Health Center.The research design is Case Control. Case samples of patients with hypertension were 25 and controls did not suffer from 25 respondents who were taken by purposive sampling technique. Primary data collection was obtained through interviews and secondary data obtained from monthly reports of hypertension. Univariate analysis to see the frequency distribution and bivariate to see the relationship (Chi Square) and the magnitude of risk factors (OR).The results showed that there was a relationship between family history, p value = 0.041 (OR = 6.469 95% CI; 1.230-23.012) with the incidence of hypertension and there was no relationship between gender, p value=0.064 (OR= 4.125 95%CI; 1.092-15.585) with the incidence of hypertension.Suggestions for a healthy lifestyle by reducing the consumption of foods that contain high sodium and doing enough physical activity.